The effect of local irradiation on lung tumor formation in Af mice - Veyalkina, Nataliya; Fedosenko, Olga; Miadzvedzeva, Аlena (Journal of the Belarusian State University. Ecology, 2026)
Studies of the biological effects of ionizing radiation have recently become actual due to the expansion of the implement of nuclear technologies in a variety of human activities. Especially it important for using of medical imaging when human body is often exposed by low-dose ionizing radiation. Ionizing radiation at low doses is the cause of stochastic effects, which are depended on influence by many another factors, such as the genetic predisposition or chemical environmental pollutants. The aim of this study was to investigate the effect of spontaneous and chemically induced tumor formation in the lungs of Af mice after local X-ray irradiation of the thoracic region.Af mice of both sexes were 3 months old at the start of the study. Animals were irradiated using an X-Rad 320 Precision X-ray Inc. biological X-ray system. Local irradiation of the thoracic region was achieved by shielding with protective plates. Fractionated local irradiation of the thoracic region of Af mice with a total dose of 5 Gy increase the frequency of spontaneous lung tumors. Both the percentage of animals with tumors (up to 48,7% versus 27% in controls) and the number of tumors per mouse (up to 1,24 versus 0,86 in controls) grew up.Neither worsening of general health status nor growth of tumor rates were found after repeated (every two weeks for 9 months) local irradiation by radiography doses. Thus, we concluded that repeated local radiography low-dose irradiation did not affect the rate of spontaneous lung carcinogenesis in Af mice. But in combination with urethane solution repeated irradiation by radiography doses stimulated chemically induced carcinogenesis in the lungs of Af mice: increased in the number and size of tumors.
Keywords: ionizing radiation; carcinogenesis; laboratory mice; lung tumors